KEDISIPLINAN GURU DALAM PROSES BELAJARAN MENGAJAR DI UPTD SD NEGERI KENARILANG - Orlando De Rois Lapuilana (JURNAL PENDIDIKAN DAN KEGURUAN, 2025)
This study aims to determine and describe the discipline of teachers in the learning process at UPTD SD Negeri Kenarilang. The approach used in this research is qualitative descriptive type, with the subjects of the principal, teachers and students of grades I to VI. Data collection was done through passive participation observation, interviews, and documentation. The data analysis technique used was the Miles and Huberman model. The researcher tested the credibility of the data through triangulation of sources and techniques. The results showed that at the planning stage, all teachers were disciplined in making teaching modules, but the time for making them was different. At the implementation stage, teachers have been disciplined in displaying good attitudes such as fairness, politeness, and tolerance among others, but teachers still appear to lack discipline in terms of managing learning time. In the evaluation stage of learning outcomes, teachers have carried out evaluations according to applicable rules, but it seems that teachers only provide evaluations in the realm of knowledge (cognitive) only.